Estimating postmatch fatigue in soccer: The effect of individualization of speed thresholds on perceived recovery - Tomazoli, G.; Marques, J. B.; Farooq, A.; Silva, J. R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the effectiveness of different individualization methods of speed zones during match play to estimate postmatch perceptual recovery in soccer. Methods: Twelve players under the age of 19 y undertook field-based assessments to determine their maximal aerobic speed (MAS) and maximal sprint speed (MSS). External load (extracted from 10-Hz GPS over 10 official matches) was measured and classified into 4 categories as follows: low-speed running, moderate-speed running, high-speed running, and sprinting. Match running distribution into different speed zones was categorized using either MAS, MSS, MAS and MSS as measures of locomotor capacities, and absolute values. Players perceived recovery status was recorded immediately postmatch (Post) and 24 (G+24H) and 48 hours (G+48H) after each game. Results: Different individualization methods resulted in distinct match outputs in each locomotor category. Perceived recovery status was lower (P < .001) at Post (3.8 [1.32], 95% confidence interval [CI], 3.6 to 4.2), G+24H (5.2 [1.48], 95% CI, 4.9 to 5.6), and G+48H (6.0 [1.22], 95% CI, 5.7 to 6.3) compared with prematch values (7.1 [1.05], 95% CI, 6.8 to 7.3). The absolute perceived recovery-status score was better associated with high-speed running using the locomotor-capacities method at Post (ß = -1.7, 95% CI, -3.2 to -0.22, P = .027), G+24H (ß = -2.08, 95% CI, -3.22 to -0.95, P = .001), and G+48H (ß = -1.32, 95% CI, -2.2 to -0.4, P = .004) compared with other individualization methods. Conclusion: The authors` results suggest that locomotor capacities may better characterize the match intensity distribution (particularly for the high-speed running and sprinting categories) and should be preferred over MAS and MSS to estimate perceived recovery.